2021
DOI: 10.3390/cancers13040818
|View full text |Cite
|
Sign up to set email alerts
|

Plexin-B3 Regulates Cellular Motility, Invasiveness, and Metastasis in Pancreatic Cancer

Abstract: The Plexins family of proteins are well-characterized transmembrane receptors of semaphorins, axon guidance cue molecules, that mediate the cell attraction or repelling effects for such cues. Plexins and their ligands are involved in numerous cellular activities, such as motility, invasion, and adhesion to the basement membrane. The detachment of cells and the gain in motility and invasion are hallmarks of the cancer metastasis cascade, thus generating interest in exploring the role of plexins in cancer metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Interestingly, it has been previously reported that PLXNB3 KD in pancreatic cancer negatively impacted cancer tumor growth in vivo while increasing cancer cell migration and metastasis. 58 We therefore conclude that PLXNB3's role is tumor-dependent and may be influenced by ligand interaction. The partner of interaction for PLXNB3 in TNBC is currently unknown.…”
Section: Crispr-induced Plxnb3 Downregulation Negatively Impacts In V...mentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, it has been previously reported that PLXNB3 KD in pancreatic cancer negatively impacted cancer tumor growth in vivo while increasing cancer cell migration and metastasis. 58 We therefore conclude that PLXNB3's role is tumor-dependent and may be influenced by ligand interaction. The partner of interaction for PLXNB3 in TNBC is currently unknown.…”
Section: Crispr-induced Plxnb3 Downregulation Negatively Impacts In V...mentioning
confidence: 71%
“…Several reports indicate that PLXNB3 signaling is involved in actin cytoskeleton remodeling and cell motility. We therefore investigated if PLXNB3 downregulation impacts TNBC cell migration. Cancer cells grown as spheroids can invade the extracellular matrix in which they are embedded .…”
Section: Resultsmentioning
confidence: 99%
“…Prior reports and data mining indicate PLXNB3 is mostly absent from normal tissues, and its expression in adult tissues is restricted primarily to the central nervous system ( Figure 2C and Figures S2A/B ), making PLXNB3 an attractive target for novel therapies. PLXNB3 mutations have been described in breast cancer, pancreatic cancer, melanoma and prostate cancer (Liu et al, 2015; Saxena et al, 2021). In breast cancer, increased PLXNB3 mRNA expression was observed in moderately and poorly differentiated tumors compared to well-differentiated tumors (Malik et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate PLXNB3 signaling is involved in actin cytoskeleton remodeling and cell motility (Li et al, 2012; Li and Lee, 2010; Saxena et al, 2021). We therefore investigated if PLXNB3 downregulation impacts TNBC cell migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation